An optimal design model for tunnel lighting systems - Li, Shu Guang; Tu, Gang; Zhou, Qinghua (Optik (Stuttgart), 2021)
We propose an optimal design model for determining light sources, powers, layout modes, and equipment spacing of lamps in tunnels that not only effectively reduce the overall installation & operation cost and bus also ease the complexity of manual calculations during the design process of tunnel lighting systems. Firstly, the optimal objective functions considering the construction & installation and energy consumption cost are given in the design of tunnel lighting systems; secondly, the design constraints of tunnel lighting systems are analyzed, which include the demand and design brightness, the minimum and maximum equipment spacings and so on. Then, in order to compare the differences between different optimal design parameters, an enumeration algorithm is proposed. Finally, the YanPengShan tunnel in Leshan City, Zhejiang province, is taken as an example to analyze the influence of different design parameters of tunnel lighting systems on the overall cost of the system under various conditions.